Inquilinitermes johnchapmani, a New Termite (Isoptera: Termitidae: Termitinae) from the Llanos of North Central Bolivia - Rudolf H Scheffrahn (Universidade Estadual de Feira de Santana, 2014)
Inquilinitermes johnchapmani is described from soldiers and workers collected in the Llanos de Mojos of Bolivia. This is the fourth and the smallest species of the genus. Unlike its congeners, I. johnchapmani is not an inquiline of Constrictotermes spp. nests although an association with Cornitermes snyderi nests is likely.